Formation of family values among preschoolers in preschool conditions - Pozdniakova A. A., Pustoutova T. D. (Modernization of educational and upbringing process in preschool educational institution)
The article deals with the significance of the formation of family values in preschool children in the conditions of preschool educational institution. The theoretical foundations necessary for successful education of children in love and respect for family, its traditions and history are investigated.
Keywords: Семья; дошкольники; семейные ценности; дошкольная образовательная организация; family; preschoolers; family values; preschool educational organisation